2004
DOI: 10.1007/s00425-003-1150-0
|View full text |Cite
|
Sign up to set email alerts
|

Introns are key regulatory elements of rice tubulin expression

Abstract: The genomic clones containing elements that regulate transcription of the three known rice (Oryza sativa L.) alpha-tubulin isotypes (Ostua1, Ostua2 and Ostua3) have been isolated. We have used these genomic regions to identify the regulatory elements that contribute to the expression of a marker gene (gusA) in transient assays performed on rice calli derived from mature embryos. In all cases, we found that the first intron was required to achieve high levels of expression. This is consistent with data already … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
51
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(52 citation statements)
references
References 47 publications
1
51
0
Order By: Relevance
“…In recent years, intronic regulatory elements (IREs; Yutzey et al 1989) have been identified which function as enhancers, repressors and promoters of gene transcription (Busch et al 1999;Deyholos and Sieburth 2000;Kapranov et al 2001;Fiume et al 2004). In many cases, IREs reside within the first intron (Wang et al 2002;Gazzani et al 2003;Michaels et al 2003;Fiume et al 2004). …”
Section: Intronic Regulatory Elementsmentioning
confidence: 99%
“…In recent years, intronic regulatory elements (IREs; Yutzey et al 1989) have been identified which function as enhancers, repressors and promoters of gene transcription (Busch et al 1999;Deyholos and Sieburth 2000;Kapranov et al 2001;Fiume et al 2004). In many cases, IREs reside within the first intron (Wang et al 2002;Gazzani et al 2003;Michaels et al 2003;Fiume et al 2004). …”
Section: Intronic Regulatory Elementsmentioning
confidence: 99%
“…We can only speculate about the functional significance of this region, but it is, for instance, possible that intron 3 contains cis-regulatory elements involved in regulating the expression of phyB2. Such regulatory elements have been identified in introns of other plant genes (e.g., Fiume et al 2004).…”
Section: Discussionmentioning
confidence: 99%
“…However, not all introns can enhance gene expression and not all genes are influenced by introns in their pattern of expression (Rethmeier et al 1997). In rice, a regulatory function for introns has been demonstrated for members of the tubulin gene family (Fiume et al 2004). The mechanism of IME is not yet understood, but an involvement of the splicing machinery is probable (Rose and Beliakoff 2000;Clancy and Hannah 2002).…”
Section: Intron Role In Expression Enhancementmentioning
confidence: 99%